EFFECT OF SPRAYS NUMBER AND FOLIAR MICRONITE 35 ON GROWTH AND YIELD OF PEPPER UNDER UNHEATED GREEN HOUSE - Jaffar, S.A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted during the season of 2014 - 2015 inside unheated green house to investigate the effect of sprays number and different concentrations of micronite 35 (0.0, 1.0, 2.0, 2.5 and 3.0 cm3 .l-1) and their interaction on growth and yield of Pepper var. California Wonder with using (RCBD) with three replicates. Results showed that the sprays number and the concentrations of micronite 35 and their interaction had a significant effect on all the characteristics that studied. The interaction of three sprays with 3 cm3 .l-1 of micronite 35 gave the highest average of plant height (103.12cm), branches number.plant-1 (11.61), leaves number.plant-1 (107.41) leaf area.plant-1,(121.31dc2) flowers number (80.96) and set of flowers percentage (92.403). Results also gave the highest average of fruits number.plant-1, fruit long, fruit weight, yield-1. plant, early yield, and yield /greenhouse that were (38.81, 11.63cm, 80.99gm, 3.143kg, 0.229ton, 6.034ton) respectively. While the average was 10.86 fruits number.plant-1, 5.08cm fruit long, 30.71g. fruit weight, 0.333 kg. yield. Plant-1, 0.136ton early yield and 0.639ton yield.greenhouse-1 respectively at compared with control treatment.